2007
DOI: 10.1111/j.1600-0501.2007.01419.x
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of resonance frequency analysis to evaluate dental implant stability: simulation and histomorphometrical animal experiments

Abstract: Although RF did not correlate with histological implant-bone contact, the present results demonstrated that a connection between the implant and bone at the neck region of the implant affects RF the most effectively, further suggesting the superiority of RFA in the process of implant treatment and the follow-up. The present results could explain the discrepancy between RFA and other parameters of implant stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
84
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 22 publications
12
84
1
3
Order By: Relevance
“…Though some studies have shown that secondary stability is correlated to the surface properties of dental implants (19), the present findings did not support this theory. Other factors, such as strong bone anchorage (18,24), stiffness of the surrounding bone (2,18,19), type of implant used and surgical technique (18,25) may support the current results. Nevertheless, the increases in RFA values that occur during implant healing and have been attributed to increased bone anchorage cannot be explained by histomorphometric data (18,25).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Though some studies have shown that secondary stability is correlated to the surface properties of dental implants (19), the present findings did not support this theory. Other factors, such as strong bone anchorage (18,24), stiffness of the surrounding bone (2,18,19), type of implant used and surgical technique (18,25) may support the current results. Nevertheless, the increases in RFA values that occur during implant healing and have been attributed to increased bone anchorage cannot be explained by histomorphometric data (18,25).…”
Section: Discussionsupporting
confidence: 52%
“…Other factors, such as strong bone anchorage (18,24), stiffness of the surrounding bone (2,18,19), type of implant used and surgical technique (18,25) may support the current results. Nevertheless, the increases in RFA values that occur during implant healing and have been attributed to increased bone anchorage cannot be explained by histomorphometric data (18,25). As observed in this study, no correlations between histomorphometric parameters of osseointegration and ISQ values could be identified by other authors (2,18,24,25).…”
Section: Discussionsupporting
confidence: 52%
“…Ito et al (2008) similarly found that resonance frequency analysis did not correlate with histological bone-to-implant contact but also concluded that the connection between the implant and bone at the neck region of the implant affects the value significantly. Hence they considered that the resonance frequency analysis was useful for monitoring implant osseointegration clinically.…”
Section: Resonance Frequency Analysismentioning
confidence: 99%
“…Also, the rod and the test surface must maintain 0.6-2.0mm distance and if the distance is over 5mm, the measured value may be insignificant. (Ito, et al 2008, Schulte 1988. Periotest ® has limited clinical use since it cannot measure the mesiodistal mobility and the position and angle of the rod affects the measured value.…”
mentioning
confidence: 99%